2007
DOI: 10.1177/0310057x0703500107
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the AMBU® Laryngeal Mask and the LMA Classic in Anaesthetised, Spontaneously Breathing Patients

Abstract: There may be a role for single-use laryngeal mask airways with concerns about inability to adequately sterilise laryngeal mask airways to eradicate prion proteins. A single-blinded prospective randomised controlled trial was conducted to compare the clinical performance of the single-use AMBU ® LMA with the reuseable LMA Classic. There was no difference in time to insertion, successful insertion at first attempt, oropharyngeal leak pressure, haemodynamic response to insertion or complications of placement. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 19 publications
4
15
1
Order By: Relevance
“…Both devices performed similarly in establishing an adequate airway with first insertion (success rates AMBU 85%, LMAU 82%) and this is similar to other recent studies [10, 11, 13, 20]. There was a single failure within the AMBU group when there was easy insertion but inability to ventilate [10, 20].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Both devices performed similarly in establishing an adequate airway with first insertion (success rates AMBU 85%, LMAU 82%) and this is similar to other recent studies [10, 11, 13, 20]. There was a single failure within the AMBU group when there was easy insertion but inability to ventilate [10, 20].…”
Section: Discussionsupporting
confidence: 87%
“…There was a single failure within the AMBU group when there was easy insertion but inability to ventilate [10, 20]. Ng and Shariffuddin have hypothesized that these failures may be due to epiglottic downfolding on insertion of the AMBU [10, 20]. This is further supported effective ventilation following insertion with an LMAC, which has epiglottic aperture bars to prevent such an occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary outcomes were successful insertion at first attempt, oropharyngeal leak pressure, haemodynamic changes on insertion, and complications of LMA placements. Sample size was based on earlier studies of AMBU and LMA insertion in nonparalysed, anaesthetized patients [3, 4]. Prospective power analysis showed that a sample size of 50 patients per group would be required to detect a 30% difference in the primary outcome at a significance level of 5% and power of 80%.…”
Section: Methodsmentioning
confidence: 99%
“…All these features make its insertion easier than CLMA™. [14] Furthermore, unlike CLMA™ it lacks epiglottic aperture bars.…”
Section: Discussionmentioning
confidence: 99%
“…With an increasing concern for transmission of prion diseases, use of single devices like ALM™ is being advocated. [1415] Furthermore, we wanted to investigate that whether unaided placement of ALM™ would have any advantage over finger aided placement of CLMA™ in terms of post-ETT/LM exchange haemodynamic response, ease of placement, fibre-optic view, coughing/bucking, and post-operative sore throat.…”
Section: Discussionmentioning
confidence: 99%